Energy Distribution of Secondary Electrons from Gold on Teflon-FEP - Fonzar Pintao, Carlos Alberto [UNESP] (2016)
This paper presents results of the spectrum of energy of secondary electrons for the energies of perpendicularly incident electrons of 0.4 keV, 2.0 keV, or 3.5 keV in a gold surface deposited on a substratum of Teflon-FEP. Two samples of Teflon-FEP (50 nm) were used with deposition by sputtering gold layers with thicknesses of 2.5 nm and 50 nm. The results show that the energy distribution depends on the energy of irradiation for the sample with the 2.5 nm gold layer, while no significant difference was observed for the sample with the 50 nm layer.